A proposal for sentiment analysis on twitter for tourism-based applications - Guzmán De Núñez, Xiomarah Maria; Núñez-Valdez, Edward Rolando; Pascual Espada, Jordán; González-Crespo, Rubén; Garcia-Díaz, Vicente (Frontiers in Artificial Intelligence and Applications, 2020)
People rely on other people’s opinions to make decisions, especially if they belong to their circle of trust. In addition, there are lots of websites of recognized prestige that provide people opinions about different products and services, which are read by millions of people before making a decision. That is why systems for sentiment analysis are becoming increasingly important to automatically process the information and determine feelings of users. They analyze their written words, usually conditioned by the characteristics of microblogging platforms, in which a large number of messages are published every day, providing a great source of information, impossible to be managed manually. In this work, we show a proposal to analyze the feeling that Twitter users have towards different hotels or hotel chains through a platform that could be easily adapted to other contexts. The goal is to create q a structure based on independent and interchangeable components that will make it possible to conduct studies in a more uniform, open and transparent way.
Ponencia de la conferencia "17th International Conference on New Trends in Intelligent Software Methodology Tools and Techniques, SoMeT 2018; Granada; Spain; 26 September 2018 through 28 September 2018"
Keywords: bayesian network; domain-dpecific language; eTourism; machine learning; sentiment analysis; soft computing; Scopus(2); WOS(2)